Adventures in Zambezia - Thornley, Wayne; Cook, Andrew; Silverston, Anthony; Forrest, Stuart (Film producer); Buckland, Mike.; Suarez, Jeremy, 1990-; Breslin, Abigail, 1996-; Nimoy, Leonard; Goldblum, Jeff, 1952-; Jackson, Samuel L.; Triggerfish Animation Studios; Cinema Management Group; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
An adventurous young falcon named Kai leaves his remote country home for Zambezia, the fabulous city of birds, against his father's wishes. When his father is captured by an evil lizard who plans to attack the city, Kai must learn the importance of teamwork to rescue his father and save his new friends.
DVD; region 1; 5.1 Dolby Digital, 1.78:1 anamorphic widescreen.
Dialogue in English, French (Quebec) or Spanish with optional subtitles in English, French or Spanish; English SDH.
Jeremy Suarez, Abigail Breslin, Leonard Nimoy, Jeff Goldblum, Samuel L. Jackson, Richard E. Grant, Jennifer Lewis, Jim Cummings.
Music by Bruce Retief.
Special features: 4 featurettes: Birds of a feather; An African story; The tree city; Technical challenges and 1 music video: Come fly with me.
Keywords: Falcons -- Juvenile films; Birds -- Mozambique -- v; Fathers and sons -- Juvenile films; Lizards -- Juvenile films; v; Falcons -- Drama; Birds -- Mozambique -- v; Fathers and sons -- Drama; Lizards -- Drama; v; Falcones -- 2 -- idex; Aves -- 2 -- idex; Padre e hijo -- 2 -- idex; Birds; Falcons; Fathers and sons; Lizards; Mozambique -- 2; Animated films; Feature films; Video recordings for the hearing impaired; Children's : Animated Feature; Films; Juvenile works